FROM GLOBAL BEST PRACTICES TO NATIONAL IMPLEMENTATION: DIGITAL HEALTH STRATEGIES FOR AZERBAIJAN - Bahar Graefen; Nadeem Fazal (Problems of Information Society)
The rapid evolution of digital technologies has created unprecedented opportunities for transforming healthcare systems worldwide. Experiences from countries such as Estonia, Sweden, Singapore, and China demonstrate how digital tools – including electronic health records, telemedicine, mobile health, and artificial intelligence – can enhance healthcare accessibility, quality, and efficiency. This thesis explores digital health's role in addressing healthcare challenges and its adaptation to the Azerbaijani context. Although Azerbaijan has initiated digital reforms like e-prescriptions and telemedicine, significant challenges remain, including infrastructural gaps, regulatory needs, and digital literacy barriers. This study analyses the current landscape, identifies key obstacles and opportunities, and offers strategic recommendations. By leveraging global best practices and investing in infrastructure, capacity building, and governance, Azerbaijan can build a resilient, equitable digital health ecosystem that advances public health goals. In an era of increasing global interconnectedness, the adoption of digital health strategies by Azerbaijan holds considerable potential for enhancing the effectiveness of its health system, thereby contributing to the improvement of population health outcomes. Furthermore, this initiative will play a pivotal role in ensuring the country's preparedness for future public health challenges.